Case-finding for COPD clinic acceptability to patients in GPs across Hampshire: a qualitative study - Danielle Rose; Emma Ray; Rachael H. Summers; Melinda Taylor; Helen Kruk; Mal North; Kate Gillett; Mike Thomas; Tom M. A. Wilkinson (npj Primary Care Respiratory Medicine, 2021)
Abstract Despite high mortality and morbidity, COPD remains under-diagnosed. Case-finding strategies are possible, but patients’ perspectives are unexplored. Using qualitative methods, we explored the patient perspective of a case-finding intervention among at-risk patients in primary care. Semi-structured telephone interviews were transcribed and thematic analysis utilised. Seven patients without (mean age 64.5 years (58–74), n = 4) and 8 with obstructed spirometry (mean age 63.5 (53–75), n = 4) were interviewed. Themes identified were motives, challenges and concerns regarding attending the clinic. These included wanting to be well; to help with research; concern over negative impact to life from COPD diagnosis; perceived utility of the clinic; quality of information given; staff manner, approachability and knowledge; and perceived effects of the clinic on lifestyle, self-management and symptoms. The intervention was generally deemed useful and reassuring, although shared information was too detailed or irrelevant for some. Several reported positive lifestyle changes, improved symptoms and improved self-management.